Diagnosis and management of primary autoimmune neutropenia in children: insights for clinicians - Farruggia, Piero (Ther Adv Hematol, 2015)
Autoimmune neutropenia of infancy (AIN), also called primary autoimmune neutropenia, is a disease in which antibodies recognize membrane antigens of neutrophils, mostly located on immunoglobulin G (IgG) Fc receptor type 3b (FcγIIIb receptor), causing their peripheral destruction. It is the most frequent type of neutropenia in children under 3–4 years of age and in most cases shows a benign, self-limited course. The diagnosis is based on evidence of indirect antineutrophil antibodies, whose detection frequently remains difficult. In this review we have analyzed the literature regarding AIN and present our personal experience in diagnosis and management.